2022
DOI: 10.2105/ajph.2022.306932
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Individuals at Risk for Hereditary Breast and Ovarian Cancer: A Statewide Initiative, Georgia, 2012–2020

Abstract: Georgia implemented a statewide family history screening program for hereditary breast and ovarian cancer. From November 2012 through December 2020, 29 090 individuals were screened, 16 679 of whom (57.3%) self-identified as a racial/ethnic minority. Of the 4% (1172/29 090) of individuals who screened as high risk, more than half underwent genetic consultation (793/1172; 67.7%) and testing (416/589; 70.6%). Compared with White women, Black and Hispanic women had higher uptake rates of genetic consultation. Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Furthermore, rural populations in Georgia bear the brunt of the state's cancer burden. 71.1% of Georgia's population, living in 149 of 159 counties, are medically underserved according to state defined criteria, and nearly 54% (85/159) of Georgia's counties are classified as rural based on the 2013 Rural-Urban Continuum Codes (16,17). Georgia's cancer mortality hotspots are concentrated in the eastern Piedmont to Coastal Plain, southwestern rural Georgia, and northern rural Georgia (16).…”
Section: Cancer Care In Georgiamentioning
confidence: 99%
“…Furthermore, rural populations in Georgia bear the brunt of the state's cancer burden. 71.1% of Georgia's population, living in 149 of 159 counties, are medically underserved according to state defined criteria, and nearly 54% (85/159) of Georgia's counties are classified as rural based on the 2013 Rural-Urban Continuum Codes (16,17). Georgia's cancer mortality hotspots are concentrated in the eastern Piedmont to Coastal Plain, southwestern rural Georgia, and northern rural Georgia (16).…”
Section: Cancer Care In Georgiamentioning
confidence: 99%
“…A universal feature of population screening is that most of those screened will be found to be at low genetic risk. In the case of HBOC, this is 85–95% of those who complete family history screening [ 15 ]. In our prior work, we found that African American women were more likely than white women to misunderstand negative HBOC screening results to mean they were at lower risk for breast cancer, rather than accurately understanding they were at lower risk for carrying a genetic mutation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%